2016
DOI: 10.3171/2015.12.focus15583
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ventriculoperitoneal shunt placement in the treatment of idiopathic intracranial hypertension: an analysis of neuroendoscopy, frameless stereotaxy, and intraoperative CT

Abstract: OBJECTIVE Cerebrospinal fluid shunting can effectively lower intracranial pressure and improve the symptoms of idiopathic intracranial hypertension (IIH). Placement of ventriculoperitoneal (VP) shunts in this patient population can often be difficult due to the small size of the ventricular system. Intraoperative adjuvant techniques can be used to improve the accuracy and safety of VP shunts for these patients. The purpose of this study was to analyze the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Such accurate catheter placement may be more easily achieved with intraoperative navigation for VPS. Previous studies [ 11,[14][15][16][17][18][19] have reported the use of ultrasound, frameless stereotaxy, neuroendoscopy and navigation to increase the accuracy of ventricular catheter placement and to improve long-term outcomes for patients with hydrocephalus. A systematic review by Flannery [ 20] showed that there was insufficient evidence to recommend the use of neuroendoscopy for routine VPS.…”
Section: Discussionmentioning
confidence: 99%
“…Such accurate catheter placement may be more easily achieved with intraoperative navigation for VPS. Previous studies [ 11,[14][15][16][17][18][19] have reported the use of ultrasound, frameless stereotaxy, neuroendoscopy and navigation to increase the accuracy of ventricular catheter placement and to improve long-term outcomes for patients with hydrocephalus. A systematic review by Flannery [ 20] showed that there was insufficient evidence to recommend the use of neuroendoscopy for routine VPS.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate catheter placement may be more easily achieved when intraoperative navigation is used during VPS. Previous studies [11,[14][15][16][17][18][19] have reported the use of ultrasound, frameless stereotaxy, neuroendoscopy and navigation to increase the accuracy of ventricular catheter placement and improve long-term outcomes in patients with hydrocephalus. A systematic review by Flannery [20] showed that there was insufficient evidence to recommend the use of neuroendoscopy for routine VPS.…”
Section: Discussionmentioning
confidence: 99%
“…Various intraoperative adjuvant techniques have been employed in addressing the challenges of accurately cannulating the undersized ventricular system in IIH. These include the use of ultrasound guidance, neuronavigation, neuroendoscopy and intraoperative computed tomography (CT) [15]. In our case we used the It is recommended that pregnant patients with IIH should be managed in the same way as any other patient with IIH.…”
Section: Discussionmentioning
confidence: 99%